Mobile marketing as an antecedent of creating brand awareness in South Africa - Lamola, Medupi John (My University, 2019)
The use of social networking sites as enablers of engagement between people is growing as more people are getting access to technology. Researchers in developed countries have studied how people engage on social networking sites and the role played by brands in that engagement (Hollebeek, Glynn & Brodie, 2014). A lot still needs to be uncovered in emerging markets like South Africa to bridge the knowledge gap that exists. The aim of this study was to investigate if mobile marketing was an antecedent of creating brand awareness in South Africa. It fills a gap in emerging markets that showed apathy by brands and marketers alike in adopting social networking sites as strategic business tools, hoping this technology would disappear (Maduku, Mpinganjira, Mercy, 2016). The variables of user experience and social media usage were examined to see if they influenced online consumer engagement. Online consumer engagement was studied to determine if it had any influence on brand awareness. An online survey was conducted using Qualtrics software to collect data from 223 respondents through convenience sampling method. A quantitative analysis of collected data was statistically examined by running multiple linear regression, studying correlation between variables, analysing variance and observing coefficients as well as using graphs to plot the results. The results revealed that mobile marketing was indeed an antecedent of creating brand awareness. The study proved that user experience and social media usage had an influence on online consumer engagement respectively, and so did online consumer engagement on brand awareness, thus supporting the findings by Hollebeek et al,.(2014). It is recommended that marketers should leverage mobile marketing and other opportunities brought by social networking sites to create brand awareness. Future research should consider the influence that other elements of digital marketing such as social media management, search engine optimisation, online advertising, etc. have on brand as well as on engagement (Hollebeek, Glynn & Brodie, 2014; Tsai & Men, 2013; Yoo Donthu & Lee, 2000). Researcher should study other available social networking sites in emerging markets such as MySpace, WeChat, Tumblr, etc. to observe online consumer engagement and brand awareness in those networking sites (Hollebeek et al, 2014; Pfeil, Arjan, & Zaphiris, 2009). Researchers should also conduct qualitative research with social networking sites users to explore the perceptions of different age groups. Keywords: Social networking sites, mobile marketing, social media marketing, user experience, social media usage, online consumer engagement, brand, brand awareness, digital marketing, emerging markets
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing Johannesburg, 2019
Keywords: Mobile commerce; Internet marketing; Cell phones--South Africa